Genomic Insights of Halophilic Planococcus maritimus SAMP MCC 3013 and Detail Investigation of Its Biosurfactant Production - Waghmode, Samadhan; Suryavanshi, Mangesh; Dama, Laxmikant; Kansara, Shraddha; Ghattargi, Vikas; Das, Parijat; Banpurkar, Arun; Satpute, Surekha K. (Frontiers in Microbiology, 2019)
Moderate halophilic bacteria thrive in saline conditions and produce biosurfactant (BS) which facilitates the oil scavenging activity in the oil polluted surroundings. Production of such unusual bioactive molecules plays a vital role for their survival in an extreme and adverse environment. Current research deals with isolation of Planococcus maritimus strain SAMP MCC 3013 from Indian Arabian coastline sea water for BS production. The bacterium tolerated up to 2.7 M NaCl demonstrating osmotic stress bearable physiological systems. We used integrated approach to explore the genomic insight of the strain SAMP and displayed the presence of gene for BS biosynthesis. The genome analysis revealed this potential to be intrinsic to the strain. Preliminary screening techniques viz., surface tension (SFT), drop collapse (DC) and oil displacement (OD) showed SAMP MCC 3013 as a potent BS producer. BS reduced SFT of phosphate buffer saline (PBS) pH: 7.0 from 72 to 30 mN/m with a critical micelle concentration (CMC) value of 1.3 mg/mL. Subsequent investigation on chemical characterization, using thin layer chromatography (TLC), Fourier transform infrared spectroscopy (FT-IR), Nuclear magnetic resonance (1H NMR and 13C NMR), Liquid Chromatography Mass Spectrometry (LC-MS) revealed terpene containing BS having sugar, lipid moieties. The genomic sequence analysis of P. maritimus SAMP showed complete genes in the pathway for the synthesis of terpenoid. Probably terpenoid is the accountable backbone molecule for the BS production, but the later stages of terpenoid conversion to the BS could not be found. Moreover, it is important to highlight that till today; no single report documents the in-detailed physico-chemical characterization of BS from Planococcus sp. Based on genomic and functional properties, the term terpene containing BS is denoted for the surfactant produced by P. maritimus.